The appearances of Jack Londonwork into the Kazakh language (Eurasian Journal of Philology Science and Education, 2019)
The article deals with the translations of Jack London’s work into the Kazakh language. Alsohighlightstranslation equivalents and difference of target text and its Kazakh translators. In addition, the peculiarityof the writer’s work and the meaningful accuracy with the translation text are compared in the analysis.